Stability, security, and the social determinants of health - Diana L. Aguirre; Casey Perez; Edwin K. Burkett (Taylor & Francis Group, 2022)
Social determinants of health are an important aspect of improving health outcomes. Militaries have deployed global health engagement activities to meet security objectives from peacetime through post-conflict. Two frameworks, the Social Model of Health and the U.S. Institute of Peace Strategic Framework for Stabilisation and Reconstruction, have similarities and are reviewed in this paper. Drawing similarities between the two presents opportunities for targeted, well-planned global health engagement activities that may bring stronger health outcomes. Military global health efforts must work with civil affairs experts and civilian partners within the host nation health context to target the most amenable social determinants of health elements that may enhance security and stability in that society.